2020
DOI: 10.1101/2020.08.24.20176792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal increase in D614G mutation of SARS-CoV-2 in the Middle East and North Africa: Phylogenetic and mutation analysis study

Abstract: Phylogeny construction can help to reveal evolutionary relatedness among molecular sequences. The spike (S) gene of SARS-CoV-2 is the subject of an immune selective pressure which increases the variability in such region. This study aimed to identify mutations in the S gene among SARS-CoV-2 sequences collected in the Middle East and North Africa (MENA), focusing on the D614G mutation, that has a presumed fitness advantage. Another aim was to analyze the S gene sequences phylogenetically. The SARS-CoV-2 S gene … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Another mutation was S477I detected in Tangerang, western border of Jakarta. Other studies reported this S477 substitution but in different residue S477G ( 20 ) and S477R in Egypt ( 19 ).…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Another mutation was S477I detected in Tangerang, western border of Jakarta. Other studies reported this S477 substitution but in different residue S477G ( 20 ) and S477R in Egypt ( 19 ).…”
Section: Discussionmentioning
confidence: 64%
“…This mutation tends to increase in many countries, as also reported by Sallam et al that D614G mutation predominates in the Middle East and North Africa. It was noticed the escalation percentage from 63.0% in February to 98.5% in four months later ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations